The PTB interacting protein raver1 regulates alpha-tropomyosin alternative splicing. - Gromak, N; Rideau, A; Southby, J; Scadden, A; Gooding, C; Hüttelmaier, S; Singer, R; Smith, C (2003)
Regulated switching of the mutually exclusive exons 2 and 3 of alpha-tropomyosin (TM) involves repression of exon 3 in smooth muscle cells. Polypyrimidine tract-binding protein (PTB) is necessary but not sufficient for regulation of TM splicing. Raver1 was identified in two-hybrid screens by its interactions with the cytoskeletal proteins actinin and vinculin, and was also found to interact with PTB. Consistent with these interactions raver1 can be localized in either the nucleus or cytoplasm. Here we show that raver1 is able to promote the smooth muscle-specific alternative splicing of TM by enhancing PTB-mediated repression of exon 3. This activity of raver1 is dependent upon characterized PTB-binding regulatory elements and upon a region of raver1 necessary for interaction with PTB. Heterologous recruitment of raver1, or just its C-terminus, induced very high levels of exon 3 skipping, bypassing the usual need for PTB binding sites downstream of exon 3. This suggests a novel mechanism for PTB-mediated splicing repression involving recruitment of raver1 as a potent splicing co-repressor.